Pengaruh Aktivasi Naoh Terhadap Biosorben Spent Mushroom Substrate (SMS) - Shinta Nurdiyanti; Elvi Yenie; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Spent mushroom substrate (SMS) generated as waste by mushroom industries after the harvesting of mushroom. SMS is one of the most organic waste generated from agricultural waste that contain lignocelluloses and can be used in modifed for the adsorption of dyes, pollutants and heavy metals. In this study, SMS was modified using sodium hydroxide (NaOH) and prepared as biosorbents. NaOH can be an efficient and economical modifier for lignocelluosic material. This study aims to determine the effect of the effect on NaOH concentration and contact time of iodine activation number and SMS surface area.Keywords: Biosorbent, NaOH, Spent Mushroom Substrate.